PENGARUH PERSEPSI KONSUMEN, FASILITAS DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (STUDI DI ROYAL MULIA RESIDENCE MEKARSARI RAJEG PADA PT. GRIYA RAJEG SENTOSA) - Marcelino Aria Putra; William Widjaja (Publika Citra Media, 2026)
This study aims to analyze the influence of consumer perception, facilities, and location on the decision to purchase a house at Royal Mulia Residence, Mekarsari Rajeg, developed by PT. Griya Rajeg Sentosa. The method used in this research is a quantitative approach with survey techniques, where data is collected through questionnaires distributed to prospective buyers. Data analysis is conducted using multiple linear regression to test the proposed hypothesis. The research results show that all independent variables, namely consumer perception, facilities, and location, have a positive and significant impact on purchasing decisions. Specifically, location has proven to be the most dominant factor influencing purchasing decisions, followed by consumer perception and facilities. These findings indicate that potential buyers highly consider the aspect of strategic location and the developer's reputation in their decision-making process. This research provides important contributions to developers in formulating moreeffective marketing strategies, emphasizing the importance of building positive perceptions and improving location accessibility. In addition, the results of this study are also expected to serve as a reference for future research in the field of consumer behavior in the property sector.